Fatty acyl chains of phosphatidyl choline and ethanolamine as diacyl, alkyl and alkenyl forms during in vitro capacitation of goat spermatozoa - DHANDA, SUMAN; ATREJA, S K (The Indian Journal of Animal Sciences, 2011)
The fluidity of sperm plasma membrane increases during capacitation and acrosome reaction as these processes involve the remodeling of many proteins and phospholipid components. Therefore, we were interested in comparing the fatty acyl chains associated with phosphatidylcholine (PC) and phosphatidylethanolamine (PE) in capacited and acrosome reacted spermatozoa of goat. PC and PE were separated from total phospholipids (PL) during in vitro capacitation and acrosome reaction. Radyl acetates were prepared from diradyl derivatives after phospholipase C treatment of PC and PE in the presence of pyridine and acetic anhydride. The corresponding fatty acyl chains were analysed by gas liquid chromatography (GLC) in diacyl, alkenyl and alkyl radyl acetate by separation and methyl ester preparation. C12, C14: 0, C16: 0, C18: 0, C20: 0 and C24: 0 are saturated and C16: 1, C18: 1, and C20: 4 were the main unsaturated fatty acyl chains. Moreover, the major fatty acyl chains of spermatozoa are different from those of surrounding fluid during the course of in vitro capacitation and acrosome reaction. The results clearly indicated the rapid turnover of these 2 sperm phospholipids in terms of active deacylation and reacylation reactions. These changes would definitely alter the sperm fertilizing ability. This may also generate bioactive PLs, viz. autocoids, fusogens, cis-unsaturated fatty acids, secondary messengers and detergents to accomplish the processes preceeding and succeeding fertilization.m